Cis amazonicus sp. nov. (Coleoptera: Ciidae) from North Brazil, with notes on the Cis tricornis species-group - Lopes-Andrade, Cristiano; Sandoval-Gómez, Vivian Eliana (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Cis amazonicus sp. nov. is described based on specimens collected in Belém, in the state of Pará, and Manaus, in the state of Amazonas, North Brazil. The new species belongs to the Cis tricornis species-group and is characterized by a suboval body with total length of 0.94-1.20 mm, almost glabrous on dorsum, with single, confuse fine punctation on pronotum and elytra and smooth interspaces of punctures; males possess a cephalic horn projected upward, slightly bifurcated at apex, and two pronotal horns projected forward; tegmen bears a V-shaped emargination at apex; penis is elongate and about 1.4x as long as tegmen. Comments are provided on other species of the Cis tricornis group.